Pengaruh Pembelajaran CIRC Berbantuan Mind mapping terhadap Hasil Belajar Materi Siklus Air pada Siswa Kelas IV Sekolah Dasar - Rossy Samita Settey (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by mind mapping on the learning outcomes of fourth-grade students at SD Negeri 7 Lubai on the water cycle. The method used was a quasi-experimental design with a nonequivalent control group. The study sample consisted of two classes: the experimental class (using the CIRC model assisted by mind mapping) and the control class (using conventional learning). Data were obtained through pretests and posttests, then analyzed using an independent sample t-test with the help of SPSS version 26. The results showed that the average posttest score of students in the experimental class was higher (80.65) than in the control class (71.56). A significance value of 0.022 <0.05 indicates a significant effect of the CIRC model assisted by mind mapping on student learning outcomes. Thus, the application of the CIRC learning model assisted by mind mapping has proven effective in improving students' understanding and learning outcomes on the water cycle. Keywords: CIRC; mind mapping; learning outcomes; water cycle; science learning